DEVELOPMENT OF PROBLEM BASED LEARNING (PBL) CHEMISTRY LEARNING MODULE ON SOLUBILITY AND SOLUBILITY PRODUCTS IN CLASS XI SMA NEGERI 15 MEDAN - Freddy Tua Musa Panggabean; Juan Samuel Simanjuntak; Harvei Desmon Hutahaean; Jamalum Purba; Ani Sutiani (INFOKUM, 2022)
This study aims to determine the development of a chemistry learning module based on Problem Based Learning (PBL) on Solubility and Solubility Products in Class XI SMA Negeri 15 Medan. The sample in this study consisted of one class consisting of 30 students who were taught using the Problem Based Learning model. The instrument used is a test in the form of essay questions. The results showed that 1) the learning module based on Problem Based Learning on the material solubility and solubility product of chemistry learning which was developed based on expert judgment had met the BSNP eligibility standard, the average validation results obtained an average content feasibility score (3.84), the feasibility language (3.75), feasibility of presentation (3.75) and feasibility of graphics (3.76); 2) based on the assessment of teacher and student responses that have met the BSNP eligibility standards obtained based on material (3.84), appearance (3.87) and benefits (3.69); 3) student learning outcomes after being taught using Problem Based Learning chemistry learning modules are higher than the KKM (75) with an average of 81.07.